PENERAPAN MEDIA PEMBELAJARAN COMPUTER BASED INSTRUCTION (CBI) DALAM PENINGKATAN AKTIFITAS DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMAN 1 KOTA JAMBI - NIRMALA NIRMALA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to apply Computer Based Instruction (CBI) learning media in an effort to improve student achievement in economics subjects for class X students at SMA Negeri 1 Jambi City in the 2021/2022 academic year. This research method is CAR (Classroom Action Research) with four stages, namely planning, implementation, observation and reflection. The study population used all students of class X at SMA Negeri 1 Jambi City in the academic year 2021/2022 and the subjects of this study were 34 students who were taken randomly (random sampling). The use of CBI (Computer Based Instruction) learning media in Economics learning can improve student learning achievement by looking at the results of tests carried out in two cycles, where the pre-action student achievement results with an average of 68 and student learning completeness of 67% experiencing an increase in the cycle I with an average score of 71 and student learning completeness of 83%. Further refined with the results of student achievement in the second cycle with the acquisition of an average score of 87 and student learning completeness that reaches 100%. So it can be concluded that the use of CBI (Computer Based Instruction) learning media is an alternative in an effort to improve student achievement in economics subjects for class X MIPA 3 at SMA Negeri 1 Jambi City in the 2021/2022 academic year. ABSTRAKPenelitian ini bertujuan untuk menerapkan media pembelajaran Computer Based Instruction (CBI) dalam upaya meningkatkan prestasi belajar siswa pada mata pelajaran ekonomi siswa kelas X di SMA Negeri 1 Kota Jambi tahun pelajaran 2021/2022. Metode penelitian ini adalah PTK (Penelitian Tindakan Kelas) dengan empat tahapan yaitu perencanaan, pelaksanaan, observasi dan refleksi. Populasi penelitian menggunakan seluruh siswa kelas X di SMA Negeri 1 Kota Jambi tahun pelajaran 2021/2022 dan subjek penelitian ini yaitu 34 siswa yang diambil secara acak (random sampling). Penggunaan media pembelajaran CBI (Computer Based Intruction) dalam pembelajaran Ekonomi dapat meningkatkan prestasi belajar siswa dengan melihat hasil tes yang dilaksanakan dalam dua siklus, dimana pra tindakan hasil prestasi belajar siswa dengan rata–rata 68 dan ketuntasan belajar siswa sebesar 67% mengalami peningkatan pada siklus I dengan perolehan nilai rata–rata 71 dan ketuntasan belajar siswa sebesar 83%. Selanjutnya disempurnakan dengan hasil prestasi belajar siswa pada siklus II dengan perolehan nilai rata–rata 87 dan ketuntasan belajar siswa yang mencapai 100%. Maka dapat disimpulkan penggunaan media pembelajaran CBI (Computer Based Intruction) merupakan salah satu alternative dalam upaya meningkatkan prestasi belajar siswa pada mata pelajaran ekonomi kelas X MIPA 3 di SMA Negeri 1 Kota Jambi tahun pelajaran 2021/2022.